Chemical composition of Citrus spp. and oral antimicrobial effect of Citrus spp. peels essential oils against Streptococcus mutans - Aripin, Dudi; Julaeha, Euis; Dardjan, Murnisari; Cahyanto, Arief (Universitas Padjadjaran, 2015)
Introduction: The essential oils of orange peels had a considerable potential to be used as an antimicrobial agent. The aim of this present study is to analized chemical composition of Citrus spp. And the oral antimicrobial effect of Citrus spp. peels essential oils against Streptococcus mutans. Methods: Five orange peels species were used in this study consist of Lime (Citrus aurantifolia), Tangerine (Citrus nobilis), Sweet Orange (Citrus sinensis), Lemon (Citrus limon), and Kaffir Lime (Citrus hystrix). The isolated essential oils were analyzed using gas chromatography-mass spectroscopy (GC-MS). The Streptococcus mutans ATCC 25175 was employed against the antimicrobial effect of samples. Results: The extraction yields of hydrodistilled-essential oils from Tangerine, Kaffir Lime, Sweet Orange, Lemon, and Lime provided the extraction yields of 4.20, 2.26, 1.97, 1.74 and 0.83% yields, respectively. Major component essential oils of Citrus spp. was D-Limonene. The highest antimicrobial activity against S. mutans was Lime peel essential oil, followed by Lemon, Kaffir Lime, and Sweet Orange or Tangerine. All samples showed antimicrobial activity against S. mutans with the variation of antimicrobial action depending on the constituent of D-Limonene, β-Pinene, and α-terpineol. Conclusion: Major component chemical composition of essential oils of Citrus spp. was D-Limonene and antimicrobial activity by Lime peel essential oil due to its proportional amount of D-limonene and β-pinene and the highest antimicrobial activity.